Most wanted : the revolutionary partnership of John Hancock & Samuel Adams - Marsh, Sarah Jane (Disney · Hyperion, 2020)
"John Hancock and Samuel Adams were an unlikely pair of troublemakers. Hancock was young and dashing. Adams was old and stodgy. But working together, they rallied the people of Boston against the unfair policies of Great Britain and inspired American resistance. And to King George, they became a royal pain. When the British army began marching toward Lexington and Concord, sending Hancock and Adams fleeing into the woods, the two men couldn't help but worry--this time, had they gone too far? Rich with historical detail and primary sources, this spirited tale takes readers through ten years of taxes and tea-tossing, tyranny and town hall meetings. The team behind Thomas Paine and the Dangerous Word reunites for a lively look at the origins of the American Revolution told through the powerful partnership of two legendary founders."--Amazon.com.